A COMPARISON OF INTRAVENOUS ONDANSETRON AND PALONOSETRON IN PREVENTING POST-OPERATIVE NAUSEA AND VOMITING AFTER LAPAROSCOPIC CHOLECYSTECTOMY - A RANDOMIZED DOUBLE-BLIND STUDY - Kumar, Ajay; Adhana, Sumita; Dwivedi, Puneet (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Post-operative nausea and vomiting (PONV) is a frequently experienced complication following laparoscopic cholecystectomy. This study was planned to compare the antiemetic efficacy of palonosetron with ondansetron in patients undergoing laparoscopic cholecystectomy. Methods: A total of 100 patients undergoing laparoscopic cholecystectomy were randomized into two groups. Group O (n=50) received ondansetron (8 mg) and Group P (n=50) received palonosetron (0.075 mg) 3 min before induction of anesthesia. Post-operatively, patients were assessed for the occurrence of nausea, retching, or vomiting at 0–2, 2–6, 6–24, 0–24, and 24–48 h time intervals. The overall incidence of PONV in time frame (0–48 h) was determined. The need of rescue antiemetic, side effect profile, and patient satisfaction scores were also assessed. Results: The incidence and severity of nausea at all the time intervals were comparable in the two groups. The incidence of vomiting was significantly less in Group P as compared to Group O in 0–2 h (2% vs. 14%, p=0.027) and 0–24 h time intervals (10% vs. 30%, p=0.012). The overall incidence of PONV in 0–48h was lesser in Group P as compared to Group O (28% vs. 50%, p=0.024). Rescue antiemetic was required in greater number of patients in Group O as compared to Group P (p=0.038). Side effect profile and patient satisfaction scores were comparable in the two groups. Conclusion: Palonosetron is better than ondansetron in lowering the overall incidence of PONV in 0–48 h time interval, in patients undergoing laparoscopic cholecystectomy.